Efforts To Improve Learning Outcomes In Chemistry in Class X Students Using the Discovery Method Through Laboratory Activities on the Concept of the Collide System at SMK Negeri 6 Samarinda - Nur Fithria, Nimas (Educationist: Journal of Educational and Cultural Studies, 2022)
This study aims to improve chemistry learning outcomes in class X students with the discovery method through laboratory activities on the colloid system concept. The subjects of this study were students of class X Mining Geology (GP) 1 at SMK Negeri 6 Samarinda from May to June 2022. The method used in this study was classroom action research with a sample of 33 students who were taught with methods of discovery through laboratory activities. Classroom Action Research which conducted the study consisted of two cycles with each cycle includes the stages in the planning, implementation, observation, and reflection. The research instrument used is the observation sheet, questionnaire, achievement test, and interviews of teachers and students. From the research, this paper shows the study had reached the criteria has become a boundary indicator of the success demonstrated by the increase in categories of aspects of active student participation in learning in each cycle. Similarly, an increase in achievement test average score of 68.09 in the first cycle increased to 74.81 and no more students who scored less than 60.00. Similar to the results of interviews of students who responded positively to the learning process that uses a method of discovery through laboratory activities. From these results we can conclude that learning by using learning method of discovery through laboratory activities can enhance students' learning outcomes chemistry.